Thematic Approach of Mathematics Textbooks in the Primary School - Helmane, Ineta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article describes and analyzes theoretical materials, textbooks about the aspects of the thematic choice in the acquisition of mathematics content using the thematic approach in primary school. Teaching mathematics thematically emphasises the use of applications of mathematics around a central theme whereas teaching in topics predominantly emphasises mathematical content. Mathematics content in the framework of the thematic approach is associated with the development of skills in practical activities the so called ‘hands on’ as well as the correlation of the acquired knowledge based on the theme or a concept; also, skills that can be applied in lifetime actions as well as the development of a personal sound attitude, values and goals. In the thematic approach mathematics content involve objects, information, topics and themes. The topicality should be linked with happenings in their personal lives as well as the latest developments in community life, socio-economic processes or a scientific context as well.